Biobased carbon-supported palladium electrocatalysts for borohydride fuel cells - Martins, Marta; Sljukic, Biljana; Sequeira, Cesar A. C.; Metin, Onder; Erdem, Mehmet; Sener, Tansel; Santos, Diogo M. F. (Pergamon-Elsevier Science Ltd, 2016)
Designing highly active and cost-effective electrocatalysts is essential for accelerating commercialization of fuel cell technology. In this work, oxygen reduction reaction (ORR) and borohydride oxidation reaction (BOR) are both investigated on monodisperse palladium nanoparticles (Pd NPs) supported on Vulcan XC72 as well as on two prepared carbon materials obtained from different biosources, namely grape stalk activated carbon (GSAC) and vine shoots activated carbon (VSAC). The electrocatalysts are characterized using TEM and XRD and their activity for ORR and BOR in alkaline media is studied using linear scan voltammetry with rotating ring-disk electrode. ORR and BOR onset potentials and number of exchanged electrons reveal significantly higher activity of the Pd NPs supported on biobased carbons compared to the one supported on Vulcan XC72. Pd/GSAC shows good activity towards direct 4-electron ORR, whereas Pd/VSAC electrocatalyst has improved performance for BOR. Namely, number of exchanged electrons in ORR at Pd/GSAC and Pd/VSAC was evaluated to be approximately 4 and 2, respectively. Conversely, number of exchanged electrons in BOR was found to be 2.0 and 5.6 for Pd/GSAC and Pd/VSAC, respectively. (C) 2016 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Palladium nanoparticles; Biobased carbon support; Oxygen reduction reaction; Borohydride oxidation reaction; Rotating ring-disk electrode